Seminar Penyuluhan “Menjadi Pemuda Berkarakter melalui Pemahaman Pergaulan Bebas” - Yanto, Yanto; Bashori, Abdul Hamid; Holis, Holis; Rofiqi, Rofiqi; Rizal, Moh.; Rizal, A.; Alim, Abd. (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib, 2024)
Degradation of ethics and morality during adolescence poses a threat that can hinder or even jeopardize the future of teenagers. This counseling is conducted to provide education and a deep understanding of how teenagers can build strong morals and develop positive adolescent ethics. The counseling uses the PAR approach with the aid of media such as laptops, LCD projectors, and materials as primary tools for conveying information. The results of the counseling show: the event was conducted very well, with excellent interaction between the presenter and participants. The presenter effectively and smoothly delivered information about ethics and morality, the causes of their decline, and strategies for prevention. Conclusion: The counseling on ethics and morality has a positive psychological impact as participants are able to understand the material well.